2018
DOI: 10.1093/jas/skx015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with vegetable oils, including castor oil, on milk production of ewes and on growth of their lambs1

Abstract: The objectives in this experiment were to compare the effects of castor oil, canola oil, or sunflower oil on lactation performance, milk composition, and milk fatty acid (FA) profile in Santa Inês ewes and on growth of lambs. Forty-four ewes (66.9 ± 4.7 kg of initial BW, mean ± SD) were penned individually with their lambs and used in a randomized complete block design with 11 blocks and four diets. The experimental diets were as follows: 1) basal diet without added oil (control), 2) 30 g FA/kg DM of canola oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Recently, Lodi et al (2019) reported that the inclusion of 12.5 mg of monensin kg -1 of DM increased ruminal pH without affecting DMI or feed behavior of lambs fed high-concentrate diets. In some cases, the use of 25 mg of monensin aims to control coccidiosis (Polizel et al, 2017;Parente et al, 2018); however, few studies evaluate whether the inclusion of lower rates can control coccidiosis in small ruminants.…”
Section: Itemmentioning
confidence: 99%
“…Recently, Lodi et al (2019) reported that the inclusion of 12.5 mg of monensin kg -1 of DM increased ruminal pH without affecting DMI or feed behavior of lambs fed high-concentrate diets. In some cases, the use of 25 mg of monensin aims to control coccidiosis (Polizel et al, 2017;Parente et al, 2018); however, few studies evaluate whether the inclusion of lower rates can control coccidiosis in small ruminants.…”
Section: Itemmentioning
confidence: 99%
“…However, this recommendation is mostly based on knowledge gained from dairy cows and might be related to the susceptibility of this species to milk fat depression (MFD) induced by unsaturated FA (especially when high-concentrate diets are fed) [ 6 , 12 ]. On the contrary, there is evidence that dairy ewes are not prone to this MFD type [ 3 , 8 , 13 , 14 ]. Thus, in the ovine, substitution of 16:0-rich fats by oils of higher unsaturation degree (e.g., rapeseed or soybean oils) may provide advantages that go beyond enhancing production level, specifically by modulating milk FA profile [ 7 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…RA is not expected to be synthesized in rumen; however, it could be found in milk depending on the type of animal feeding. As a matter of fact, about 90% of the fatty acid content of castor oil is the triglyceride formed from RA, and castor oil may supplement cow feeding [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%